Hubungan Persepsi dan Tingkat Kebutuhan Perawatan Ortodonti Berdasarkan Dental Aesthetic Index (DAI) Pada Mahasiswa FKG UMI - Bima, Lukman; Pamewa , Kurniaty; Novawaty , Eva; Zaliha , Mar’ahtun (Seroja Husada: Jurnal Kesehatan Masyarakat, 2025)
Malocclusion is defined as an abnormal occlusion characterized by an inappropriate relationship between the maxilla and mandible, which can cause several problems, namely masticatory, periodontal, swallowing, impaired oral function, and psychosocial problems related to aesthetics. Aesthetics on the face determines self-perception and can affect quality of life. Orthodontic treatment is a form of treatment in the field of dentistry whose role is to improve the arrangement of teeth so as to improve mastication, phonetic and aesthetic abilities. The Dental Aesthetic Index (DAI) is a normative instrument that is widely used in epidemiological studies to assess the need for orthodontic treatment. This index assesses in a record the physical and esthetic features of the occlusion determined along the scale and severity of the malocclusion. The DAI links clinical and aesthetic components mathematically to produce a single score that combines the physical and aesthetic aspects of the occlusion. Research objective: To find out the relationship between perception and the level of need for orthodontic treatment based on the Dental Aesthetic Index (DAI) in UMI FKG students Batch 2019-2021. Methods: This study uses a cross sectional method with an analytic descriptive research design. The research sample was UMI Faculty of Dentistry students Class of 2019-2021 who fulfilled 88 samples. Results: Based on the Spearman test to see the relationship between perception and the level of need for orthodontic treatment based on the Dental Aesthetic Index (DAI) in FKG UMI students Batch 2019-2021 showed a p-value of 0.001 (p <0.05) meaning that there was a significant relationship between perception and level orthodontic treatment needs. Conclusion: there is a significant relationship between perception and the level of need for orthodontic treatment based on the Dental Aesthetic Index (DAI) in UMI Faculty of Dentistry students Class of 2019-2021.